Multiple brown tumors caused by a parathyroid adenoma mimicking metastatic bone disease from giant cell tumor - Rohit Phulsunga; Rahul Parghane; Rajendra Kanojia; Debasis Gochhait; Ashwani Sood; Anish Bhattacharya; Bhagwant Mittal (World Journal of Nuclear Medicine)
Brown tumor affects multiple bones in the body with variable clinical symptoms, which may be misdiagnosed as multiple bone metastases or primary bone tumor. In the present case report, we report the usefulness of 99mTc-MDP bone scan and 99mTc-MIBI whole body scan in differentiating brown tumor of hyperparathyroidism from giant cell tumor.